PENGEMBANGAN APLIKASI PENDETEKSI OBJEK UNTUK TUNANETRA MENGGUNAKAN OPERATOR TEPI CANNY DENGAN LIBRARY OPENCV BERBASIS ANDROID - teguh pradana; Eko Hajianto Sula (SPIRIT, 2023)
Abstract: conducted by the Central Bureau of Statistics of East Java Province in 2019 stated that the number of blind people in the Pasuruan City/Regency was 273 people. From the results of the survey, the highest number of blind people is in the Pasuruan district. Smartphone and internet users in Indonesia by early childhood reached 29%. The use of android smartphones cannot be separated from human activities or activities during the Covid- 19 pandemic. The development of the Object Detection Application uses the waterfall method, in making the application using Android Studio with the Java programming language. By utilizing Canny Edge Operator Image Processing by optimizing the OpenCV Library, then using ML Kit to optimize object types